2013
DOI: 10.1002/cbin.10170
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia induces adipocyte differentiation of adipose‐derived stem cells by triggering reactive oxygen species generation

Abstract: Generation of reactive oxygen species (ROS) by NADPH oxidase 4 (Nox4) induces the proliferation and migration of adipose-derived stem cells (ASCs). However, the functional role of mitochondrial ROS (mtROS) generation in ASCs is unknown. Therefore, we have investigated whether hypoxia induces the differentiation of ASCs via ROS generation. We also have tried to identify the cellular mechanisms of ROS generation underlying adipocyte differentiation. Hypoxia (2%) and ROS generators, such as antimycin and rotenone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…We have previously demonstrated that hypoxia significantly increases the proliferation of ASCs via NADPH oxidase 4-generated reactive oxygen species (ROS) [34,35]. Hypoxia also accelerated the adipogenic differentiation of ASCs via mitochondrial ROS generation [29]. In addition, vitamin C significantly increased ASC proliferation through the mitogen-activated protein kinase pathway and enhanced the hair-growth promoting effect of ASCs [10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously demonstrated that hypoxia significantly increases the proliferation of ASCs via NADPH oxidase 4-generated reactive oxygen species (ROS) [34,35]. Hypoxia also accelerated the adipogenic differentiation of ASCs via mitochondrial ROS generation [29]. In addition, vitamin C significantly increased ASC proliferation through the mitogen-activated protein kinase pathway and enhanced the hair-growth promoting effect of ASCs [10].…”
Section: Discussionmentioning
confidence: 99%
“…After the medium was changed to AIM, the cells were cultured for 2 weeks with MA. Oil Red O staining was used to assess the lipid accumulation in ASCs [29].…”
Section: Adipocyte Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondria-targeted antioxidants such as mitoCP prevent both the adipogenic differentiation and the associated increase in ROS, whereas the addition of exogenous H 2 O 2 to mitoCP-treated hMSCs rescues adipogenic differentiation [34]. Similarly, hypoxia stimulates adipocyte differentiation by enhancing the production of mitochondrial ROS [85]. On the other hand, both exogenous H 2 O 2 and oligomycin-dependent inhibition of mitochondrial activity inhibit the osteogenic differentiation of hMSCs.…”
Section: Figmentioning
confidence: 99%
“…On the other hand, P2Y 1 receptor is a heterotrimeric G-protein-coupled receptor and activates G(q) and therefore robustly promotes inositol lipid signaling responses (21). Considering that the activation of phosphoinositide-3-kinase (PI3K)-Akt pathway stimulates adipogenic differentiation (13,26), it is possible that the PI3K-Akt pathway is involved in extracellular ATP-stimulated TG accumulation via P2Y 1 receptor. Furthermore, cellsurface F 1 F 0 -ATP synthase is concentrated in lipid rafts (12,25).…”
Section: Extracellular Atp Is Responsible For the Cell-surface F 1 F mentioning
confidence: 99%